Non-bullous diffuse cutaneous mastocytosis. - Garofalo, L. (European Journal of Pediatric Dermatology, 2022)
Like other proliferative disorders of the first months of age that predominantly affect the skin – infantile hemangioma, juvenile xanthogranuloma, Langerhans cell histiocytosis – mastocytosis has a broad clinical spectrum that can range from a single skin lesion – mast cell tumor – to more or less numerous skin lesions – maculo-papular mastocytosis or urticaria pigmentosa – up to the involvement of the whole skin area – diffuse mastocytosis – and exceptionally to the involvement of other organs – systemic mastocytosis –.